An adaptable different-levels cascaded h-bridge inverter analysis for PV grid-connected systems - Adnan Hussein Ali; Hassan Salman Hamad; Ali Abdulwahhab Abdulrazzaq (Institute of Advanced Engineering and Science, 2019)
Multi-level inverters (MLIs), have gained popularity in the last few years as a result of their low total harmonic distortions (THD) as well as their output waveform which is of high quality. The converter which considers more appropriate for applications of photovoltaic (PV)beyond the varying MLIs arrangementsis the Cascaded H-Bridge-(CHB) (MLI), meanwhile each PV panel may be served as an independent DC supply for any CHB unit. Through the use of MATLAB/Simulink, the efficiency of symmetrical single phase MLI in terms of the number of switches, harmonic content in addition to the stresses of voltage through theswitches that exist at photovoltaic cell by means of input source is enhanced; varying parameters like output current, voltage and power, and THD at 5-level 7-level and 9-level Cascaded MLI are observed. In this paper, attention is paid to a multi-level topologies which is flexible and based on cascaded MLI intended for PV grids connected system. An observation of the output voltage becomes closer to the sine wave as the levels increase, while the increase in the levels of Cascaded Multilevel Inverter causes the total harmonic distortion to decrease.